Respuesta :
Answer:
[tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx = \frac{1}{e}[/tex]
General Formulas and Concepts:
Calculus
Limits
Limit Property [Addition/Subtraction]: [tex]\displaystyle \lim_{x \to c} [f(x) \pm g(x)] = \lim_{x \to c} f(x) \pm \lim_{x \to c} g(x)[/tex]
Limit Property [Multiplied Constant]: [tex]\displaystyle \lim_{x \to c} bf(x) = b \lim_{x \to c} f(x)[/tex]
Differentiation
- Derivatives
- Derivative Notation
Derivative Property [Multiplied Constant]: [tex]\displaystyle \frac{d}{dx} [cf(x)] = c \cdot f'(x)[/tex]
Basic Power Rule:
- f(x) = cxⁿ
- f’(x) = c·nxⁿ⁻¹
Integration
- Integrals
Integration Rule [Fundamental Theorem of Calculus 1]: [tex]\displaystyle \int\limits^b_a {f(x)} \, dx = F(b) - F(a)[/tex]
Integration Property [Multiplied Constant]: [tex]\displaystyle \int {cf(x)} \, dx = c \int {f(x)} \, dx[/tex]
U-Substitution
Step-by-step explanation:
Step 1: Define
Identify
[tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx[/tex]
Step 2: Integrate Pt. 1
- [Integral] Rewrite [Improper Integral]: [tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx = \lim_{b \to \infty} \int\limits^b_1 {e^{-x}} \, dx[/tex]
Step 3: Integrate Pt. 2
Identify variables for u-substitution.
- Set u: [tex]\displaystyle u = -x[/tex]
- [u] Differentiate [Basic Power Rule, Derivative Properties]: [tex]\displaystyle du = -dx[/tex]
- [Bounds] Switch: [tex]\displaystyle \left \{ {{x = b ,\ u = -b} \atop {x = 1 ,\ u = -1}} \right.[/tex]
Step 4: Integrate Pt. 3
- [Integral] Rewrite [Integration Property - Multiplied Constant]: [tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx = \lim_{b \to \infty} -\int\limits^b_1 {-e^{-x}} \, dx[/tex]
- [Integral] U-Substitution: [tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx = \lim_{b \to \infty} -\int\limits^{-b}_{-1} {e^u} \, du[/tex]
- [Integral] Rewrite [Limit Property - Multiplied Constant]: [tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx = -\lim_{b \to \infty} \int\limits^{-b}_{-1} {e^u} \, du[/tex]
- [Integral] Exponential Integration: [tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx = -\lim_{b \to \infty} e^u \bigg| \limits^{-b}_{-1}[/tex]
- Evaluate [Integration Rule - Fundamental Theorem of Calculus 1]: [tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx = -\lim_{b \to \infty} \big( e^{-b} - e^{-1} \big)[/tex]
- Rewrite: [tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx = -\lim_{b \to \infty} \bigg( \frac{1}{e^b} - \frac{1}{e} \bigg)[/tex]
- Evaluate limit: [tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx = -\bigg( 0 - \frac{1}{e} \bigg)[/tex]
- Simplify: [tex]\displaystyle \int\limits^{\infty}_1 {e^{-x}} \, dx = \frac{1}{e}[/tex]
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Integration